The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1248/bpb.b12-00183
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Effects of Gymnopilin on Circulatory System of the Rat

Abstract: Gymnopilin is one of the substances produced by the hallucinogenic mushroom, Gymnopilus junonius. In this study, we examined effects of gymnopilins purified from wild fruiting bodies of G. junonius on contractile activity of aorta preparations and blood pressure in rats. Gymnopilins at lower concentrations than 5 mg/mL did not evoke contraction of helical strips of the thoracic aorta. In contrast, gymnopilins (5 mg/ mL) applied to the aorta strips pre-contracted by norepinephrine (100 nM) caused relaxation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…We have recently reported that gymnopilins activate two intracellular signal cascades including the phospholipase C-dependent one (Miyazaki et al, 2012) and the cAMP-dependent one (Nishio et al, 2012). In addition, here we report that gymnopilins act on the nAChR.…”
Section: Junoniussupporting
confidence: 65%
See 1 more Smart Citation
“…We have recently reported that gymnopilins activate two intracellular signal cascades including the phospholipase C-dependent one (Miyazaki et al, 2012) and the cAMP-dependent one (Nishio et al, 2012). In addition, here we report that gymnopilins act on the nAChR.…”
Section: Junoniussupporting
confidence: 65%
“…We have recently reported that gymnopilins activate phospholipase C and increase intracellular Ca 2+ concentrations ([Ca 2+ ] i ) in non-neuronal cells isolated from dorsal root ganglia of the rat (Miyazaki et al, 2012), and that gymnopilins act directly on vascular smooth muscles and activated the cAMP-dependent cascade to cause the vasodilation (Nishio et al, 2012). However, direct evidence that gymnopilins act on neurons is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple effects on the various tissues and cell types may relate to different gymnopilin molecules. 154 Recently, gymnopilins have been found to directly bind to and inhibit nicotinic types of acetylcholine (Ach) receptors, which may partially explain Gs. spectabilis poisoning.…”
Section: Notorious Poisonous Mushroomsmentioning
confidence: 99%
“…Gymnopilins may be distributed into the central nervous system by crossing the blood–brain barrier and could act directly on cells in the central nervous system to excite the vasomotor center. The multiple effects on the various tissues and cell types may relate to different gymnopilin molecules . Recently, gymnopilins have been found to directly bind to and inhibit nicotinic types of acetylcholine (Ach) receptors, which may partially explain Gs.…”
Section: Notorious Poisonous Mushroomsmentioning
confidence: 99%